Synthesis of Novel Ethylene Antagonists - Sozynski, Jan Maria (Curtin University, 2022)
In search of more user-friendly ethylene antagonists, synthesis of water soluble cycloproparenes and [1,2,3]triazolo[1,5-a]pyridines were targeted for this study. A series of precursors to water soluble cycloproparenes were synthesised, however all decomposed in the final reaction. Functionalised analogues of [1,2,3]triazolo[1,5-a]pyridines were prepared and demonstrated some anatgonism of ethylene action in a series of chemical reactivity and preliminary in vivo assays.